2019
DOI: 10.1002/jcp.28863
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of macrophage subtypes by IRF5 determines osteoclastogenic potential

Abstract: Bone-resorbing osteoclasts are differentiated from macrophages (MΦ) by M-CSF and RANKL. MΦ can be mainly classified into M1 and M2 MΦ, which are proinflammatory and anti-inflammatory, respectively, but little is known about their osteoclastogenic potential. Here, we investigated the osteoclastogenic potential of MΦ subtypes. When the two MΦ subtypes were differentiated into osteoclasts using M-CSF and RANKL, M2 MΦ more potently differentiated into osteoclasts than M1 MΦ. M2 MΦ generated with IL-4 or IL-10 also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
(64 reference statements)
5
21
0
Order By: Relevance
“…M1 and M2 is a subclassification of macrophages wherein M1 macrophages are classically activated and pro‐inflammatory, whereas M2 macrophages are alternatively activated and anti‐inflammatory. ( 46 ) Recent evidence demonstrates that M2 macrophages are more efficient at osteoclastogenesis compared with M1 macrophages, ( 47 ) which is consistent with our previous report, ( 10 ) and we validated herein (Figs. 4 and 5) that OM form more osteoclasts than BM Mφ.…”
Section: Discussionsupporting
confidence: 93%
“…M1 and M2 is a subclassification of macrophages wherein M1 macrophages are classically activated and pro‐inflammatory, whereas M2 macrophages are alternatively activated and anti‐inflammatory. ( 46 ) Recent evidence demonstrates that M2 macrophages are more efficient at osteoclastogenesis compared with M1 macrophages, ( 47 ) which is consistent with our previous report, ( 10 ) and we validated herein (Figs. 4 and 5) that OM form more osteoclasts than BM Mφ.…”
Section: Discussionsupporting
confidence: 93%
“…Our SVM model predicted that IRF5 may function as a repressor of osteoclast differentiation through the activation of IRF8. Consistent with this prediction, Yang et al(2019) [23] reported that silencing IRF5 increased osteoclast differentiation. However, in this study, NFATc1 expression leads to suppression of IRF5 expression.…”
Section: Resultsmentioning
confidence: 66%
“…The training is done using the class labels, OCU and OCD, as summarized in Table 5. In addition, total 213 ChIP-seq identified putative IRF8 target genes obtained from mouse GC B cell lines [23] and 6,812 ChIP-seq identified NFATc1 target genes from Harmonizome [43] have been fed into the learned models.…”
Section: Choosing Key Genes and Incorporating Chip-seq Identified Targetsmentioning
confidence: 99%
“…A previous report showed that peritoneal macrophages from adiponectin-deficient mice express M1 markers (30). It was recently reported that M1 macrophages have inefficient osteoclastogenic potential compared to M2 macrophages (31, 32). Thus, we examined the immunological and osteoclastogenic properties of CD11b-positive osteoclast precursors from various sources including PBMCs, peritoneal cells, and bone marrow cells.…”
Section: Resultsmentioning
confidence: 99%
“…When osteoclastogenic potential and macrophage phenotypes were examined using peritoneal macrophages, lower numbers of TRAP + MNCs with higher IL-6 and lower IL-10 induction were also observed in adiponectin-deficient peritoneal macrophages compared to wild-type (Figures 5D,E), implying that adiponectin-deficient macrophages have attenuated osteoclastogenic potential with M1-like properties. We recently reported that M2 macrophages have higher osteoclastogenic potential than M1 macrophages (32). Since adiponectin-deficient osteoclast precursors had M1-like properties in the current study, we hypothesized that adiponectin-exposed osteoclast precursors could polarize into M2-like macrophages, thereby possessing high osteoclastogenic potential.…”
Section: Resultsmentioning
confidence: 99%